2020
DOI: 10.12701/yujm.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of thiopurine-induced early leukopenia in a Korean pediatric patient with Crohn’s disease who turned out to possess homozygous mutations in NUDT15 R139C

Abstract: Homozygous mutations in NUDT15 R139C are known as the major factor associated with thiopurine-induced early leukopenia, particularly in Asian patients. Therefore, NUDT15 genotyping is currently recommended before thiopurine treatment to identify patients who are NUDT15 poor metabolizers and consider the use of an alternative immunomodulatory therapy. We report a case of a 12-year-old Korean girl with Crohn’s disease (CD), in whom thiopurine-induced leukopenia was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…One of the important pharmacogenetic factors in thiopurine metabolism is associated with genetic polymorphisms of the nudix hydrolase 15 ( NUDT15 ) gene. Moriyama et al 13 observed that NUDT15 enzyme activity varied with the NUDT15 polymorphism, which is associated with leukopenia during treatment with thiopurines, particularly in Asians 14‐18 . However, data on the treatment outcomes of NUDT15 enzyme activities are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important pharmacogenetic factors in thiopurine metabolism is associated with genetic polymorphisms of the nudix hydrolase 15 ( NUDT15 ) gene. Moriyama et al 13 observed that NUDT15 enzyme activity varied with the NUDT15 polymorphism, which is associated with leukopenia during treatment with thiopurines, particularly in Asians 14‐18 . However, data on the treatment outcomes of NUDT15 enzyme activities are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moriyama et al 13 observed that NUDT15 enzyme activity varied with the NUDT15 polymorphism, which is associated with leukopenia during treatment with thiopurines, particularly in Asians. [14][15][16][17][18] However, data on the treatment outcomes of NUDT15 enzyme activities are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Another notable gene was Nudix hydrolase 15 ( NUDT15 ) which is located near CNV107 on chromosome 11. The gene of NUDT15 could encode an enzyme which is a negative regulator of thiopurine activation and toxicity [ 29 ], and a NUDT15 R139C mutation could cause thiopurine-induced early hair loss in Japanese and Korean patients [ 30 , 31 ]. Moreover, NUDT 15 c.415C > T polymorphism could also increase the risk of hair loss, as pointed out in the research of Wang et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations for NUDT15 rather than TPMT should be considered in Asia [ 224 ]. Since most studies were conducted in patients with inflammatory bowel disease, further research is needed for pediatric patients with autoimmune diseases [ 269 ].…”
Section: Treatmentmentioning
confidence: 99%
“…224 Since most studies were conducted in patients with inflammatory bowel disease, further research is needed for pediatric patients with autoimmune diseases. 269…”
Section: First-line Treatmentsmentioning
confidence: 99%